LEGALITAS OVER KREDIT (PENGALIHAN UTANG) DAN AKIBAT HUKUM BAGI DEBITUR DALAM PERJANJIAN LEASING KENDARAAN MOBIL (STUDI PADA PT. SINAR MITRA SEPADAN (SMS) FINANCE KOTA KUPANG) - Londong, Cornelis; Nubatonis, Orpa J; Dinata, Husni Kusuma (Petitum Law Journal, 2024)
Current economic development is a manifestation of national economic progress so that it is hoped that it can create a just and prosperous society. To achieve national economic development in finance, it is carried out through several economic activities, both for people and leasing companies.This research study discusses the incident of transferring debt under the hands without the knowledge of the leasing agent and being judged as not complying with the contents of the leasing agreement. With this incident, it is necessary for the public to understand the legality of legal over-credit and the legal consequences for the debtor when carrying out a transfer of debt under the hand. This research uses empirical research with qualitative methods. The results of the research show that the legal consequences of transferring debt under the hands of a car from a philosophical perspective are contrary to the theory of contractual agreements, it can have a negative impact by compensating the leasing company for losses in accordance with the Civil Code Article 1243, Article 1266 and Article 1267 for doing so. default (broken promise). Officially, the validity of overcredit (transfer of debt) from a civil law perspective has been regulated in the Civil Code in Article 1233, Article 1234, Article 1313, Article 1320, Article 1338 Paragraph (1), Article 1338 Paragraph (3), and Article 1413. If viewed from a public law angle.